The application of gas-liquid chromatography to the structural investigation of Polysaccharides - Kaplan, Morris (Department of Chemistry, 2016)
This work constitutes the first reported analysis of carbohydrate derivatives by gas-liquid chromatography, using the hydrogen-flame ionization detector. The conditions used compared favourably with conditions reported by other workers and were well suited to the quantitative analysis of methanolysis products from methylated polysaccharides. Excellent separations were achieved, and at the same time a wide range of sugars could be estimated quantitatively using a single column. The detector response was shown to be linearly related to sample size. Authenticated standards were converted to their methyl glycosides by heating with methanolic hydrogen chloride, and their relative molar responses (R ' values) to the hydrogen-flame ionization detector were determined. R values were also obtained by calculations based on recent theories accounting for the observed ionization of organic compounds in the hydrogen flame, but the calculated values were not in agreement with the R values found experimentally. The experimental results obtained suggest that, under the conditions used, the response of the sugar is related to its retention time but not to the mechanism of ionization of the sugar molecule in the flame. From the observed relationship between R values and relative retention times, relative molar responses were predicted for those sugars which were not available as standards. The possible sources of error in quantitative analysis have been discussed. Errors resulting from degradation during the methylation procedures and incomplete methylation of the polysaccharides, and from the demethylation and degradation of methylated sugars during methanolysis, were found to be greater than experimental errors arising from small variations in operating conditions and the measurement of peak areas. Using the R values already determined, the methanolysis products from twelve methylated polysaccharides were separated quantitatively by gas chromatography. The structural significance of the results obtained were discussed and possible model structures for ten of the polysaccharides investigated were presented. As far as possible, the structural models were based on the findings of previous investigations, and in those cases where published data were available, gas chromatography results were in good agreement with the published results. The hydrogen-flame ionization detector was found to be ideally suited to the analysis of methylated sugars. The greater resolving power, sensitivity of detection and, in particular, the speed with which quantitative analyses can be performed, are the major advantages which make gas-liquid chromatography superior to other techniques in this area of polysaccharide chemistry.